1976
DOI: 10.1136/jcp.29.7.587
|View full text |Cite
|
Sign up to set email alerts
|

Cellular infiltrate of the jejunum after re-introduction of dietary gluten in children with treated coeliac disease.

Abstract: SYNOPSIS Jejunal lamina propria plasma cells and eosinophils and intraepithelial lymphocytes were raised in coeliac children on gluten-containing diets, but only intraepithelial lymphocytes were increased in patients on gluten-free diets. In contrast, lamina propria lymphocytes were reduced in children with coeliac disease on gluten-containing diets but were normal in patients on gluten-free diets. In children with coeliac disease who were studied serially, lamina propria plasma cells and eosinophils and intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

1977
1977
2003
2003

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 10 publications
(28 reference statements)
1
24
0
Order By: Relevance
“…Changes in Ig-cell populations were shown to persist longer than histological damage in CD. This finding is consistent with some earlier studies [16,17], though it contradicts other reports [12,35].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Changes in Ig-cell populations were shown to persist longer than histological damage in CD. This finding is consistent with some earlier studies [16,17], though it contradicts other reports [12,35].…”
Section: Discussionsupporting
confidence: 77%
“…Sophisticated studies into IEL cell kinetics have shown that absolute IEL counts are even decreased in CD [9,22,23], due to luminopetal migration and loss. Relative IEL counts per number of epithelial cells which is in itself subject to considerable alteration in a fiat mucosa, thus can be a clinical but not a pathogenetic indicator of the enteropathy [4,16,19,24,30]. IEL counts were found to be significantly higher in CD and CMPI compared to controls.…”
Section: Discussionmentioning
confidence: 97%
“…Usually IEL have been counted in relation to a fixed number of epithelial cells (Ferguson and Murray, 1971;Otto, 1973;Lancaster-Smith et al, 1976) or to a fixed length of epithelial layer (Holmes et al, 1974). Accordingly, Ferguson (1977) has proposed that the normal range is between six and 40 IEL per 100 epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…This increase has been used both as a diagnostic indicator and to support certain immunological theories of origin of the mucosal lesion (Ferguson and Murray, 1971;Otto, 1973;Holmes et al, 1974;Lancaster-Smith et al, 1976).…”
mentioning
confidence: 99%
“…10, 1 1, 15). Quantitative changes in the number of lymphoid cells of the jejunal mucosa of untreated, treated, and glutenchallenged coeliac patients have previously been studied only by light microscopy (2, 4, 6,8,12). On the basis of these findings a number of different immune mechanisms have been suggested for the mucosal lesion (4, 6,12).…”
mentioning
confidence: 96%